Residential property price index in Croatia: from experimental to official statistics - Galinec Davor; Vuglar Jadranka; Cvrtila Dario (Croatian Review of Economic, Business and Social Statistics, 2019)
The official statistics framework is based on internationally agreed standards, taking into account the core principles of impartiality, objectivity, professional independence, cost effectiveness, statistical confidentiality, minimisation of the reporting burden and high output quality. Since the latest 2007 global economic crisis, a growing demand for more, better and timelier data under limited resources for compilers and reporting agents has been observed. The concept of experimental statistics becomes more relevant, despite the lower quality in terms of coverage, data sources and harmonised definitions. The main aim of this paper is to present the methodological development of the residential property price index in Croatia from experimental to official statistics, as well as to show corresponding changes in time, which occurred due to the changes in methodological framework, institutional responsibility for compilation, coverage and data sources. A general conclusion of the paper is that publication of non-harmonized experimental statistics results, together with explanatory metadata, is better from the point of view of users than having nothing produced by official statistics.